Pengaruh Komunikasi dan Manajemen Pengetahuan terhadap Efektivitas Kerja Karyawan Melalui Kerjasama Tim pada PT. Graha Karya Plasindo - Zulfia, Dea; Dede Sunaryo (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Communication, Knowledge Management, and Teamwork can influence employee Work Effectiveness. In this case, communication has not been optimal, knowledge management has not yet been implemented, and teamwork among employees is still lacking, which hinders work effectiveness. This study aims to determine the effect of communication and knowledge management on work effectiveness through teamwork at PT Graha Karya Plasindo. This research is a quantitative survey study. The sampling technique used in this research was saturated sampling, with a total of 87 respondents who are employees of PT Graha Karya Plasindo. The data obtained were analyzed using the PLS (Partial Least Square) technique through SmartPLS software. The results of this study indicate that: (1) Communication has a significant effect on Work Effectiveness; (2) Knowledge Management has a significant effect on Work Effectiveness; (3) Teamwork has a significant effect on Work Effectiveness; (4) Communication has a significant effect on Work Effectiveness through Teamwork; and (5) Knowledge Management has a significant effect on Work Effectiveness through Teamwork. Keywords: Communication, Knowledge Management, Work Effectiveness, Teamwork